Empowering Local Communities Through Traditional Knowledge Protection - Ayub Torry Satriyo Kusumo (Journal of World Trade Studies, 2011)
This article examines the current state of affairs with respect to local community empowerment through a traditional knowledge protection system in Indonesia, analysis of the potential impact of traditional knowledge protection management on the Indonesian economy, and making recommendations on the formulation and development of a new policy on the protection of traditional knowledge. The study is a doctrinaire research, and used a juridical approach. Secondary data were used , obtained largely through conducting a literature review of both printed and electronic materials publicly available in the library and internet. Content analysis technique based on deductive methods, was used in analyzing the data. The study came up with several findings. First, trade Related aspects of Intellectual Property Rights, Including Trade in Counterfeit Goods (TRIPs) Agreement as embodied in the provisions of the World Trade Organization (WTO) in 1994, succinctly show that Intellectual Property Rights issues are inseparable fromworld trade and investment. Secondly, protection system for traditional knowledge can be achieved by using laws that relate to Intellectual Property Rights (IPR) as well as non-IPR instruments, and using instruments other than laws. Thirdly, IPR is vitally important as it provides legal protection to commercial works.